Expanded Diversity and Host Range of Bovine Hepacivirus-Genomic and Serological Evidence in Domestic and Wild Ruminant Species - Breitfeld, Jana; Fischer, Nicole; Tsachev, Ilia; Marutsov, Plamen; Baymakova, Magdalena; Plhal, Radim; Keuling, Oliver; Becher, Paul; Baechlein, Christine (Viruses, 2022)
The hepatitis C virus (HCV)-related bovine hepacivirus (BovHepV) can cause acute as well as persistent infections in cattle. The true clinical relevance of the virus is not yet known. As reliable antibody detection methods are lacking and prevalence studies have only been conducted in cattle and few countries to date, the true distribution, genetic diversity, and host range is probably greatly underestimated. In this study, we applied several RT-PCR methods and a nano-luciferase-based immunoprecipitation system (LIPS) assay to analyze bovine serum samples from Bulgaria as well as wild ruminant sera from Germany and the Czech Republic. Using these methods, BovHepV infections were confirmed in Bulgarian cattle, with viral genomes detected in 6.9% and serological reactions against the BovHepV NS3 helicase domain in 10% of bovine serum samples. Genetic analysis demonstrated co-circulation of highly diverse BovHepV strains in Bulgarian cattle, and three novel BovHepV subtypes within the genotype 1 could be defined. Furthermore, application of a nested RT-PCR led to the first description of a BovHepV variant (genotype 2) in a wild ruminant species. The results of this study significantly enhance our knowledge of BovHepV distribution, genetic diversity, and host range.
Keywords: Cattle; Animals; skot; Germany; hepatitida C; Hepatitis C; Ruminants; host range; cattle; Genomics; genetic diversity; bovine hepacivirus (BovHepV); Host Specificity; Hepacivirus; Bulgaria; Czech Republic; přežvýkavci; distribution; zvířata; wild ruminants; hostitelská specificita; genomika